The cyclone separator application on physicochemical characterization of coconut shell-liquid smoke grade C - Angky Wahyu Putranto; Firda Puspaningarum; Sukardi Sukardi (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2020)
The further processing of coconut shell pyrolysis into liquid smoke has been developed in recent years. However, the common technology by directly condensing the smoke has many impurity compounds which decreases the yield of liquid smoke produced. Hence, in this study the cyclone separator was applied to increase the quality of physicochemical content in coconut shell-liquid smoke (CS-LS) grade C. The physical parameters analyzed were yield, pH, density and color. The chemical parameters was analyzed by GC-MS. The result showed that CS-LS processing with cyclone separator was able to increase the total yield into 3.33%, with better color, pH and density compared to the CS-LS produced using common method (direct condensation). The application of cyclone separator was also able to increase the phenolic compounds (97%), alcoholic compounds (92%), cycloalkene compounds (91%) and also decreased the benzoic acid, carbonyl and ester up to 100% compared with common method for CS-LS grade C production.